Risk factors for falls in hospitalized patients with ischemic cardiopathy - Nila Larisse Silva de Albuquerque; Milena Jamile de Assis Sisnando; Silvestre Péricles Cavalcante Sampaio Filho; Huana Carolina Cândido Morais; Marcos Venícios de Oliveira Lopes; Thelma Leite de Araujo (Rev Rene)
This study aimed to identify the presence of the Nursing Diagnosis Risk for Falls in hospitalized patients with ischemic heart disease in Fortaleza, Ceará, Brazil. This was a descriptive and quantitative study. Data collection happened from July 2010 to February 2011, through interviews, physical examination and by consulting medical records. We used an instrument to investigate the clinical and socio-demographic profile of the patients and also a check-list consisting of the Nursing Diagnosis risk factors. Of the 86 participants, 56.5% were male, mean age of 63.95 (±12.6) years. All the participants had more than two risk factors for falls, 46.5% presented six to nine concurrent risk factors. Among the investigated risk factors we identified: use of antihypertensive drugs (98.8%), visual impairment (66.3%), and sleeplessness (54.3%). Therefore, it is important for nurses to plan the care in order to prevent falls, especially for hospitalized patients with ischemic heart disease.